2016
DOI: 10.1021/acscatal.6b02842
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Release on the Ribosome Involves Substrate-Assisted Base Catalysis

Abstract: Termination of protein synthesis on the ribosome involves hydrolysis of the ester bond between the P-site tRNA and the nascent peptide chain. This reaction occurs in the peptidyl transferase center and is triggered by the class I release factors RF1 and RF2 in prokaryotes. Peptidyl-tRNA hydrolysis is pH-dependent, and experimental results suggest that an ionizable group with pK a > 9 is involved in the reaction. The nature of this group is, however, unknown. To resolve this problem, we conducted density functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 34 publications
0
24
1
Order By: Relevance
“…It remains a challenge to calculate the absolute values of redox potentials and p K a accurately; however, they can be obtained using the driving force from experimental data . Finally, we recommend a recent perspective paper by Himo, in which some of the successes and applications of the QM‐cluster approach are reviewed such as peptidyl‐tRNA hydrolysis in the ribosome (224 atoms), phenolic acid decarboxylase (> 300 atoms), and the enantioselectivity of enzymes (312 atoms). Furthermore, the author has given good examples using the QM‐cluster approach to study the origins of regioselectivity of cyanolysis and azidolysis of epoxides by haloalcohol dehalogenase and the influence of single and double mutations on the energetics of the enzymatic reaction for soluble epoxide hydrolases …”
Section: Models and Methodologiesmentioning
confidence: 99%
“…It remains a challenge to calculate the absolute values of redox potentials and p K a accurately; however, they can be obtained using the driving force from experimental data . Finally, we recommend a recent perspective paper by Himo, in which some of the successes and applications of the QM‐cluster approach are reviewed such as peptidyl‐tRNA hydrolysis in the ribosome (224 atoms), phenolic acid decarboxylase (> 300 atoms), and the enantioselectivity of enzymes (312 atoms). Furthermore, the author has given good examples using the QM‐cluster approach to study the origins of regioselectivity of cyanolysis and azidolysis of epoxides by haloalcohol dehalogenase and the influence of single and double mutations on the energetics of the enzymatic reaction for soluble epoxide hydrolases …”
Section: Models and Methodologiesmentioning
confidence: 99%
“…Kazemi et al tested several mechanisms by means of density functional theory on a reduced model of the bacterial PTC (224 atoms). 57 They concluded that a base-catalyzed mechanism, which involves a deprotonation of the P-site tRNA A76 2'-OH group, is the only one consistent with the experimental activation energies, kinetic solvent isotope effect values, and pH dependence.…”
Section: Terminationmentioning
confidence: 85%
“…Zero-point energy (ZPE) effect correction was performed at the same level as the geometry optimizations. Since the dielectric constant of the internal ribosome environment is a subject of debates, the PCM (Polarizable Continuum Model) continuum solvation model with three different dielectric constants (4, 24, and 78) was introduced to estimate for the dielectric effect [ 27 , 28 ]. The final energies reported here are the free energy barriers with the large basis set, which are corrected for ZPE and solvation effects.…”
Section: Methodsmentioning
confidence: 99%